Virtual Reality (VR) Innovation in Project Based Learning (PjBL) for Teaching English Vocabulary to Elementary Students - Rahmania Sri Untari; Rahmania Sri Untari; Yuli Astutik; Akbar Wiguna; Bobur Sabirov; Yuli Astutik; Akbar Wiguna; Bobur Sabirov (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
The urgency of this research is that the learning process is considered to require exploration and manipulation of objects in visual form to understand concepts. Students have difficulty mastering English due to its abstract and decontextual nature. The purpose of this study is to implement immersive VR with the PjBL model effectively to improve English vocabulary acquisition to understand the relationship between shape and space. The method used is User Experience (UX) Integration of Action Design Research (ADR) with the CII Framework. The number of respondents in this study was 32 students. The results showed a significant effect (Cohen's d = 3.43), paired sample t-test results (t = 14.762; p < 0.001), and an N-Gain score of 0.63. These findings prove that combining immersive VR with the PjBL model effectively improves English vocabulary acquisition, engagement, and student learning experience, and validates the CII framework as a viable approach to technology-enhanced language learning.